Self inserted foreign body in the urethra due to auroerotism - Shah, Surendra; Shrestha, Samir; Shah, Jay N (Journal of General Practice and Emergency Medicine of Nepal, 2014)
Most foreign bodies in the bladder are self inserted via urethra for autoerotic stimulation. Most of them are ashamed to admit they had introduced it for sexual gratification and diagnosis is made only when got into complication. We are reporting a case of young girl who has inserted broom stick into the urethra because of sexual curiosity and it was migrated to urinary bladder which was removed using cystoscopy. Post operative period was uneventful